Hypoxia-induced chromatin changes and ATM signalling - Olcina del Molino, M (2014)
The DNA damage response (DDR) is a complex signalling cascade triggered in response to stress, in an attempt to maintain genomic integrity. Components of this pathway, such as ATM-mediated signalling, have been proposed to act as a barrier in the early stages of tumourigenesis. Regions of low oxygen concentrations (hypoxia) occur in most solid tumours and are associated with a poor prognostic outcome. Here, we investigated the DDR induced following hypoxia-induced replication stress in an attempt to decipher the mechanism of ATM activation in response to physiological stresses that do not induce DNA damage. We hypothesized that hypoxia-mediated chromatin changes could impact on ATM signalling. We have characterised H3 methylation in response to hypoxia and found oxygen dependent changes in H3K9me3, including both global and replication fork associated increases in this histone modification. Importantly, we have found that decreases in H3K9me3 result in loss or attenuation of ATM activation. Notably, in a background of replication stress and increased H3K9me3, ATM inhibition or loss leads to accumulation of DNA damage and a significant decrease in replication rates in hypoxia. We propose that when replication stress occurs in the presence of hypoxia-induced chromatin changes, ATM activation is facilitated by the induction of H3K9me3. In this context, we propose a novel and stress specific role for ATM-mediated signalling in maintaining replication and preventing the generation of DNA breaks that may compromise genomic integrity. Moreover, the biological consequences of the hypoxia-induced chromatin context and in particular hypoxia-induced H3K9me3 include the repression of APAK, a negative regulator of p53. Activation of p53 is a key consequence of the hypoxia-induced DDR. Here we found that SETDB1, one of the H3 methyltransferases induced by hypoxia, mediates APAK repression. We propose that H3K9me3 plays a role in regulating APAK expression to allow optimal induction of p53 dependent apoptosis in hypoxic conditions suggesting a further role for H3K9me3 in facilitating DDR signalling in hypoxia. Together, these data suggest that the hypoxic chromatin context is critical for the role of the DDR as a barrier to tumourigenesis and predict that altering the chromatin landscape in combination with DNA damaging therapies would be efficacious in the treatment of hypoxic tumours.